Guidelines for the management of patients with Crohn’s disease. Recommendations of the Polish Society of Gastroenterology and the Polish National Consultant in Gastroenterology - Michał Łodyga; Piotr Eder; Magdalena Gawron-Kiszka; Agnieszka Dobrowolska; Maciej Gonciarz; Marek Hartleb; Maria Kłopocka; Ewa Małecka-Wojciesko; Piotr Radwan; Jarosław Reguła; Edyta Zagórowicz; Grażyna Rydzewska (Gastroenterology Review)
This paper is an update of the diagnostic and therapeutic recommendations of the National Consultant for Gastroenterology and the Polish Society of Gastroenterology from 2012. It contains 46 recommendations for the diagnosis and treatment, both pharmacological and surgical, of Crohn's disease in adults. The guidelines were developed by a group of experts appointed by the Polish Society of Gastroenterology and the National Consultant in the field of Gastroenterology. The methodology related to the GRADE methodology was used to assess the quality and strength of the available recommendations. The degree of expert support for the proposed statement, assessment of the quality of evidence and the strength of the recommendation was assessed on a 6-point Likert scale. Voting results, quality and strength ratings with comments are included with each statement.